Moral Decadence in Nigerian Tertiary Institutions: An Evaluator Perspective - Janet Oyebola Adetayo (Journal of Educational Sciences, 2022)
The issue of Moral Decadence is becoming worrisome not only among the Nigerian Tertiary Institutions but in the world at large and it’s gradually eroding the morals and values which has been of great benefit to people’s greatness in the past. As an evaluator, this concern leads to the conceptualization of this study that assessed the causes of moral decadence, identified those to be blamed and provide probable solutions to the menace. Three research questions guided the study and descriptive survey research design was used. Purposive sampling technique was used to select four hundred undergraduate that participated in the study. The adapted and revalidated Moral Decadence Questionnaire (MODEQ) from Olorundare (2011) study was used and it yielded reliability co-efficient of 0.88. The results reveal that Parental negligence, negative mass media contents, peer group influences, among others are the causes of moral decadence and that Parents are the most to be blamed for the level of moral decadence. To curb this menace, effective parenting, engendering positive peer influence, among others can achieve the best result. Recommendation was made, that Parents should consciously contribute to the building of a morally viable Nigerian society by instilling strong moral values into their children.